The incidence of VAT evasion - Zareh Asatryan; David Gomtsyan (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
Who benefits from the evasion of value added taxes (VAT)? Using a reform that enforced VAT on previously non-compliant large retailers in Armenia, we estimate a onethird passthrough of the tax burden on prices. This suggests that pre-enforcement evasion rents were broadly shared with consumers through lower prices. Our theoretical and empirical results explain this low passthrough rate by the supply-chain effects and second-order compliance responses of firms to VAT enforcement. Our distributional analysis shows that households at the bottom of the income distribution benefit more from the rents of evasion.
Keywords: D11; H22; H26; 330; Value added tax; Incidence; Evasion; Enforcement; Distributional Effects